Pharmacokinetic interaction between shuanghuanglian and azithromycin injection: a nonlinear mixed-effects model analysis in rats. (2nd November 2019) - Tian, Jingchen; Sun, Shusen; Zhao, Zhigang; Li, Xingang
Abstract: 1. This study aimed to evaluate the pharmacokinetic interaction of shuanghuanglian (SHL) and azithromycin in rats, and to provide experimental support for rational drug use in clinics. 2. High-performance liquid chromatography with ultraviolet detection (HPLC-UV) and high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS) approaches were respectively developed to detect the forsythiaside (active component of SHL) and azithromycin concentrations. Both non-compartmental and compartmental analyzes were employed to calculate pharmacokinetic parameters. A nonlinear mixed-effects modeling method was applied to fit the drug concentration-time data. The influence of drug coadministration on pharmacokinetic parameters was tested using forward inclusion and backward elimination procedures. 3. After drug co-administration, areas under the drug concentration–time curve (AUC) and half-lives (T1/2 ) of both azithromycin and forsythiaside increased significantly, meanwhile, the drug clearance (CL) decreased compared to single drug administration. Both forsythiaside and azithromycin exposures increased after coadministration. Two-compartment models were suitable to describe the in vivo behavior of both azithromycin and forsythiaside. The coadministration of SHL could significantly decrease the central volume of azithromycin (VCA ) and forsythiaside clearance (CLF ) decreased after co-intravenous administration of azithromycin. 4. Co-intravenous administration of forsythiaside and azithromycin could significantly increase drug exposures for both drugs. Lower dose can provide sufficient drug exposure to obtain antibacterial activity. The coadministration may be a potential method to increase therapy efficiency while decrease adverse drug reactions.